Identification of Potential Locations for Kappaphycyus alvarezii Cultivation for Optimization of Seaweed Production Based on Geographic Information Systems in Spermonde Archipelago Waters, South Sulawesi, Indonesia - Sarjito Sarjito; Hanny Ammaria; Muhammad Helmi; Slamet Budi Prayitno; Nurjannah Nurdin; Riza Yuliratno Setiawan; Parichat Wetchayont; Anindya Wirasatriya (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2022)
Indonesia is the second largest producer of red algae in the world with one of the major Kappaphycyus. alvarezii farming areas is in Spermonde Islands, Pangkep Regency, South Sulawesi Province. K. alvarezii production in Pangkep Regency increased every year. However, the availability of natural seaweed can be threatened along with the increasing demand so that seaweed cultivation is necessary. Proper site selection is crucial to guarantee the success of the seaweed farming development. A Geographic Information system (GIS) with geospatial modeling approach was applied for identification of the site selection for K. alvarezii cultivation at the Liukang Tuppabiring District, Spermonde Islands by combining various physical and chemical parameters obtained from in-situ data and hydrodynamics modeling. The parameters are Sea Surface Temperature, salinity, pH, substrate type, current speed, wave height, DO, nitrate, phosphate, and Total Suspended Solid. This research also include the accessibility and the restricted area of shipping lanes for determining the area suitability of K. alvarezii cultivation. This research demonstrates a Geographic Information system with the cell-based geospatial modeling can be effectively used and found the the suitable categorized area for K. alvarezii  is 4,546.28 ha, which is the combination of the suitable area of 4,463.08 ha and highly suitable criteria with an area of 83.2 ha. The potential productivity of wet-weight seaweed can reach 56,825 tons per cycle or 113,650 tons per year. This result suggests the GIS with geospatial modeling approach for developing the area of K. alvarezii culture can be applied in other area.